Characterization of Spirituality in Parents of Very Preterm Infants in a Neonatal Intensive Care Unit - Shanks, Vanessa; Guillen, Ursula; Mackley, Amy; Sturtz, Wendy (American Journal of Perinatology, 2022)
Objective This study aimed to characterize the spiritual beliefs, practices, and needs of parents of very preterm infants, those born <32 weeks of gestation, in a level-III NICU and to characterize parental perception of the spiritual support received in the neonatal intensive care unit (NICU).Study Design Within 14 days of their infants' birth, parents underwent a recorded semistructured interview. Responses were organized into unique themes using standard qualitative methods. Parents completed the Spiritual Involvement and Beliefs Scale (SIBS) and Spiritual Needs Inventory (SNI).Results Twenty-six parents from 17 families were interviewed and provided SIBS and SNI surveys. Interviews yielded seven major themes describing parents' spirituality and support. Most parents identified themselves as spiritual (n = 14) or sometimes spiritual (n = 2). A high SIBS score was associated with Christian religion (p = 0.007) and non-White race (p = 0.02). The SNI showed ≥80% of parents reported a “frequent” or “always” need for laughter, being with family, thinking happy thoughts, and talking about day-to-day things. The most commonly mentioned sources of spiritual support were parents' connection with a higher power through their faith (n = 12) or religious activities (n = 8). Many parents reported receiving sufficient spiritual support outside of the hospital during their unique experience in the NICU.Conclusion Parents of infants born <32 weeks of gestation in our NICU commonly self-identified themselves as spiritual. Many parents have similar spiritual needs which are often met by sources outside of the hospital.Key Points
Keywords: spirituality; NICU; parents; neonate; support; spiritual